Exploring E-Repurchase Intention of Online SMEs in Tangerang: How The Role E-Satisfaction and E-service Quality? - Dadang Munandar (Universitas Negeri Makassar, 2020)
This study aims to determine the effect of store atmosphere and service quality on purchasing decisions that have an impact on consumer loyalty at Lotte Mart in Bandung. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study Store atmosphere has a significant effect on purchasing decisions by 36.5%, hypothesis testing obtained a significance of 0.000 <0.05. Service quality has a significant effect on purchasing decisions by 44.9%, hypothesis testing obtained a significance of 0.000 <0.05. Store atmosphere and service quality simultaneously have a significant effect on purchasing decisions by 52.2%, hypothesis testing obtained a significance of 0.000 <0.05. Purchasing decisions have a significant effect on consumer loyalty by 29.0%, hypothesis testing obtained a significance of 0.000 <0.05.